Ideologi Pengarang pada Novel Mangalua Karya Idris Pasaribu - Meriah Kita Deliani Barus; Rosliani Rosliani (Balai Bahasa Sumatera Utara, 2021)
ideology on the novel Mangalua by Idris Pasaribu. The study uses qualitative descriptive methods with literary sociology. The data-gathering technique involves document and interview analysis while data analysis employs hermeneutical qualitative methods. Research has shown that it is based on cultural, historical, and socialism. From the author's biographical analysis, the maternal Idris Pasaribu has distinctive status and distinctive status. From intrinsic elements lies the theme of the Toba people's struggle for unity of groups and territory. It is this theme that maintains the intertwining of events by involving the main character, the subordinate character, the plot, and the commission. While the analysis of authors' ideologies based on the author's social ideology and the cultural background of the author is that belief, culture, the work that pervcts the author's life has contributed to the novel. Thus the stories of love, struggle, pride, culture, religion, political history were woven together in a way wrapped up in fiction reflected in the Mangalua novel by Idris Pasaribu.